Hawai Marē-oki Kaisen. - Yamamoto, Kajirō, 1902-1974.; Mimura, Akira, 1901-1985.; Tsuburaya, Eiji, 1901-1970.; Ōkōchi, Denjirō, 1898-1962.; Hara, Setsuko, 1920-2015.; Fujita, Susumu, 1912-1991. (Tōkyō : Kabushiki Kaisha Deagosutīni Japan, 2014)
Follows the career of Giichi Tomoda, a young naval pilot who participates in the 1941 attack on Pearl Harbor and successful attacks on the American and British naval fleets.
Single-sided single layer; aspect ratio 4:3.
Title from disc label.
Originally produced as a motion picture in 1942.
Director, Yamamoto Kajirō ; cinematographer, Mimura Akira ; technical director, Tsuburaya Eiji.
Ōkōchi Denjirō, Fujita Susumu, Hara Setsuko.
DVD; NTSC region 2; Dolby Digital.
Keywords: 1939-1945; Air pilots, Military -- Japan -- Drama; Pearl Harbor (Hawaii), Attack on, 1941 -- Drama; World War, 1939-1945 -- Campaigns -- Malay Peninsula -- Drama; World War, 1939-1945 -- Aerial operations, Japanese -- Drama; World War, 1939-1945 -- Naval operations, Japanese -- Drama; Air pilots, Military; Military campaigns; Military operations, Aerial -- Japanese; Military operations, Naval -- Japanese; Asia -- Malay Peninsula; Hawaii; Japan; Feature films; Fiction films; Historical films; War films; Drama; Feature films; Fiction films; Historical films; War films